Arbidol inhibits viral entry by interfering with clathrin-dependent trafficking - Blaising, Julie; Lévy, Pierre L.; Polyak, Stephen J.; Stanifer, Megan; Boulant, Steeve; Pécheur, Eve-Isabelle (Antiviral research, 2013)
Arbidol (ARB) is a broad-spectrum antiviral displaying activity against a number of enveloped and non-enveloped viruses. It was described as a viral entry inhibitor and shown to interact at the molecular level with lipid membranes and viral fusion glycoproteins to impede viral entry and fusion. However its mechanism of action at the cellular level remains unknown. Here, by using live-cell confocal imaging and the hepatitis C virus as a model virus, we show that ARB affects clathrin-mediated endocytosis by impeding dynamin-2-induced membrane scission. Moreover it induces the intracellular accumulation of clathrin-coated structures where viral particles are trapped. Collectively, our results shed light on the mechanistic aspects of ARB antiviral activity and suggest that ARB could prevent cell infection by viruses that enter through clathrin-mediated endocytosis.
Gesehen am 26.11.2020